Logos of Phenomenology and Phenomenology of the Logos. Book Five The Creative Logos. Aesthetic Ciphering in Fine Arts, Literature and Aesthetics - Tymieniecka, Anna-Teresa (Analecta Husserliana, The Yearbook of Phenomenological Research, 2006)
Having established in the ontopoiesis/phenomenology of life the creative function of the human being as the fulcrum of our beingness-in-becoming, let us now turn to investigate the creative logos. In this collection, the momentum of a gathering "creative brainstorm" leads to the vertiginous imaginative transformability of the creative logos as it ciphers through the aesthetic sense, the elements of experience - sensing, feeling, emotions, forming - in works of art, thus lifting human experience into spirit and culture.